Increasing Writing Skills Study Result Through the Experience Write a Diary In Primary School - Alafiyah, Cici Evianti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Classroom action research is conducted to address learning problems that occur in the classroom. In addition, classroom action research is also used to improve the quality of learning so that student learning outcomes can increase. This classroom action research was conducted on sixth grade students at the State Elementary School 05 Bantarbolang Pemalang. Where this classroom action research aims to improve student learning outcomes in writing skills on fiction and non-fiction text material by using the experience of writing a diary. From the results of research conducted in two cycles showed an increase. Learning outcomes in the first cycle showed a class average of 74.88 while classical learning completeness was 76.92%. The learning outcomes in the second cycle showed the class average value of 87.07 while the classical learning completeness was 100%. This proves that the use of the experience of writing a diary can improve the learning outcomes of students' writing skills. Teachers can use the experience of writing a diary to improve students' writing skills.